Pedestrian Road Accident Index for Municipalities: The Portuguese Case - Santos, Bertha (2020)
Portuguese road traffic accidents statistics show that the number of accidents with fatalities and serious injuries has in general decreased in recent years. However, the number of accidents involving pedestrians is still high when compared with those observed in other countries of the European Union. In order to assess this problem, an index of pedestrian road traffic accidents for municipalities that could be used in decision-making about pedestrian safety measures is proposed. The use of absolute values of accidents involving pedestrians (running over) does not allow itself a reliable comparison of pedestrian safety level between municipalities. In this sense, the approach proposed uses the information available in the Portuguese database PORDATA to calculate a municipal index that takes into account the degree of exposure of pedestrians to accident, based on national and municipal resident population annual growth rates and number of pedestrian's casualties. This index allows to identify the municipalities with unfavourable deviation to national numbers of road accidents involving pedestrians (per 10000 inhabitants), supporting the plan and allocation of human and economic resources for the diagnosis, definition and implementation of safety measures. The results obtained can be visualized in a GIS for a more comprehensive comparison between municipalities. The analyses performed for Portugal showed that, in general, municipalities with higher resident population annual growth rates, located mostly along the coastline and in more consolidated urban areas, tend to present better index values, which points to the need to intervene in less consolidated areas.